The effectiveness of problem-based learning (PBL) in enhancing critical thinking skills in medical education: a systematic review and meta-analysis - Su, Ting; Liu, Jing; Meng, Lele; Luo, Yijing; Ke, Qiaoling; Xie, Lingzhu (Frontiers in Education, 2025)
BackgroundProblem-based learning (PBL) has emerged as a transformative educational strategy aimed at enhancing critical thinking in medical education. While some studies suggest PBL significantly improves critical thinking skills, others show minimal differences compared to traditional teaching methods. This study aims to synthesize existing research to assess the overall effectiveness of PBL in enhancing critical thinking skills in medical education.MethodsA comprehensive literature search was conducted using PubMed, the Cochrane Library, and FMRS databases. Studies included were comparative, involving medical students, with a PBL intervention group and a conventional method control group, and assessed critical thinking skills. Data extraction and quality assessment were performed by two independent reviewers, using the Cochrane Risk of Bias Tool for RCTs and the ROBINS-I tool for non-randomized studies. Meta-analysis was conducted using Review Manager version 5.3, employing random-effect models due to high heterogeneity. Publication bias was assessed using funnel plots, Egger’s regression, and Begg’s test.ResultsEleven studies involving 14 to 267 students from various countries were included. The aggregated effect size for PBL versus conventional methods showed a significant improvement in critical thinking skills. Comparison of pre- and post-PBL critical thinking scores also indicated significant improvement post-PBL. Publication bias was assessed and found to be minimal.ConclusionPBL is significantly more effective than conventional teaching methods in enhancing critical thinking skills among medical students. These findings support the integration of PBL into medical curricula to foster critical thinking skills crucial, which are crucial for clinical practice.